Pediatric chronic myeloid leukemia in myeloid blast crisis - Biswajit Dey; Anirban Dutta (Autopsy and Case Reports, 2023)
Chronic myeloid leukemia (CML) accounts for 2-3% of childhood leukemias. About 5% of cases present in a blastic phase of CML which clinically and morphologically mimics more common acute leukemias of childhood. We report a case of a 3-yearold male who presented with gradual onset swelling of the abdomen and extremities along with generalized weakness. Examination revealed massive splenomegaly, pallor, and pedal edema. Initial workup showed anemia, thrombocytopenia, and leukocytosis (120,000/uL) with a blast percentage of 35%. Blasts were positive for CD13, CD33, CD117, CD34 and HLA-DR, and stained negative for Myeloperoxidase and Periodic Acid Schiff. Fluorescence in situ hybridization was positive for b3a2/e14a2 junction BCR-ABL1 transcript and negative for RUNX1-RUNX1T1/t(8;21), clinching the diagnosis of CML in myeloid blast crisis. The patient expired within 17 days of diagnosis and initiation of therapy.